2022
DOI: 10.1186/s13223-022-00732-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of a child with adenoidal hypertrophy and severe asthma by omalizumab: a case report

Abstract: Background Childhood adenoid hypertrophy (AH) is common and is often associated with allergic asthma, resulting in complications like obstructive sleep apnea syndrome (OSAS). Management of the disease and its complications is often challenging. Case presentation We report here a case of a 10-year-old boy who suffered from severe allergic asthma and rhinitis and was treated with omalizumab. Before the treatment, the childhood asthma control test (C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The etiology of CATD is believed to be related to infection and low immunity. 6,7 Although observational studies frequently reveal the coexistence of allergic diseases and CATD, 8,9 a definitive causal relationship remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of CATD is believed to be related to infection and low immunity. 6,7 Although observational studies frequently reveal the coexistence of allergic diseases and CATD, 8,9 a definitive causal relationship remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another case report by Sui H et al reported that the adenoid size of a 10-year-old boy with AH and severe allergic asthma significantly improved after 4 weeks of treatment with omalizumab, a monoclonal antibody used for allergic asthma. 11 Our study aimed to characterize the sensitization profiles to inhaled allergens in children with nasal complaints in urban China.…”
Section: Introductionmentioning
confidence: 99%
“…Another case report by Sui H et al. reported that the adenoid size of a 10‐year‐old boy with AH and severe allergic asthma significantly improved after 4 weeks of treatment with omalizumab, a monoclonal antibody used for allergic asthma 11 …”
Section: Introductionmentioning
confidence: 99%